1946
DOI: 10.1113/jphysiol.1946.sp004124
|View full text |Cite
|
Sign up to set email alerts
|

Urine acidity in alcohol diuresis in man

Abstract: Available evidence suggests that the diuresis following ingestion of ethyl alcohol is of the same nature as water diuresis mediated by the pituitary gland (Eggleton, 1942b). In an effort to establish further points of similarity or difference between the two types of diuresis, a class experiment on the effects of exercise on urinary excretion was performed identical with those previously reported (Eggleton, 1942a(Eggleton, , 1943 except for the substitution of alcohol as the diuretic in place of water or tea. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

1950
1950
1978
1978

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 3 publications
2
9
0
2
Order By: Relevance
“…Theoretically, the dissociation of a weak acid, such as uric acid, can be expected to decrease in acid urine, and since ethanol administration may be accompanied by acidification of the urine, this could result in enhanced reabsorption of uric acid by back diffusion of the un-ionized form. In two out of three patients given ethanol, the rise in blood lactate was accompanied by urinary acidification, as had been described before (24,32). Urinary acidification, however, does not appear to be primarily responsible for the decrease in urinary uric acid output, since, in confirmation of previous findings (33), in the patient given sodium lactate, the urine became strongly alkaline; nevertheless, lactate administration was accompanied by a decrease in urinary uric acid output and a rise in serum uric acid similar to those observed in the same patient on alcohol administration, although the urine pH was about 5 in the latter condition (see Figures 6-8).…”
Section: Discussionsupporting
confidence: 68%
“…Theoretically, the dissociation of a weak acid, such as uric acid, can be expected to decrease in acid urine, and since ethanol administration may be accompanied by acidification of the urine, this could result in enhanced reabsorption of uric acid by back diffusion of the un-ionized form. In two out of three patients given ethanol, the rise in blood lactate was accompanied by urinary acidification, as had been described before (24,32). Urinary acidification, however, does not appear to be primarily responsible for the decrease in urinary uric acid output, since, in confirmation of previous findings (33), in the patient given sodium lactate, the urine became strongly alkaline; nevertheless, lactate administration was accompanied by a decrease in urinary uric acid output and a rise in serum uric acid similar to those observed in the same patient on alcohol administration, although the urine pH was about 5 in the latter condition (see Figures 6-8).…”
Section: Discussionsupporting
confidence: 68%
“…This increment is relatively Figure 5. Observations recorded from time to time over the past 15 years (17)(18)(19) show that urine tends, irrespective of starting pH, to approach pH 6.9 at 250 C (or 6.6 at 370 C); the phenomenon has not been explained. The data show that in normal man increasing urine flow rate by water-drinking increases urinary ammonia excretion, which confirms the most systematic studies previously reported of the effect of water diuresis on ammonia excretion in unprepared, healthy, fasting humans, those made 40 years ago by Hubbard and Munford (23,24).…”
Section: Methodsmentioning
confidence: 99%
“…The most recent studies are those of Eggleton (10)(11)(12), whose subjects ingested alcohol diluted with considerable quantities of cider usually a few hours after breakfast. Her findings are in essential agreement with those to be reported below.…”
mentioning
confidence: 99%